Screening of Trypanosoma brucei gambiense in domestic livestock and tsetse flies from an insular endemic focus (Luba, Equatorial Guinea). - Carlos Cordon-Obras; Carmen García-Estébanez; Nicolás Ndong-Mabale; Simón Abaga; Pedro Ndongo-Asumu; Agustín Benito; Jorge Cano (Public Library of Science (PLoS), 2010)
BACKGROUND:Sleeping sickness is spread over 36 Sub-Saharan African countries. In West and Central Africa, the disease is caused by Trypanosoma brucei gambiense, which produces a chronic clinical manifestation. The Luba focus (Bioko Island, Equatorial Guinea) has not reported autochthonous sleeping sickness cases since 1995, but given the complexity of the epidemiological cycle, the elimination of the parasite in the environment is difficult to categorically ensure. METHODOLOGY/PRINCIPAL FINDINGS:The aim of this work is to assess, by a molecular approach (Polymerase Chain Reaction, PCR), the possible permanence of T. b. gambiense in the vector (Glossina spp.) and domestic fauna in order to improve our understanding of the epidemiological situation of the disease in an isolated focus considered to be under control. The results obtained show the absence of the parasite in peridomestic livestock but its presence, although at very low rate, in the vector. On the other hand, interesting entomological data highlight that an elevated concentration of tsetse flies was observed in two out of the ten villages considered to be in the focus. CONCLUSIONS:These findings demonstrate that even in conditions of apparent control, a complete parasite clearance is difficult to achieve. Further investigations must be focused on animal reservoirs which could allow the parasites to persist without leading to human cases. In Luba, where domestic livestock are scarcer than other foci in mainland Equatorial Guinea, the epidemiological significance of wild fauna should be assessed to establish their role in the maintenance of the infection.